Savings and prize-linked savings accounts - Kadir Atalay; Fayzan Bakhtiar; Stephen L. Cheung; Robert Slonim (Institute for the Study of Labor (IZA), 2012)
Many households have insufficient savings to handle moderate and routine consumption shocks. Many of these financially fragile households also have the highest lottery expenditures as a proportion of income. This combination suggests that Prize-Linked Savings (PLS) accounts, that combine principal-security with lottery-type jackpots, can increase savings among these at-risk households. Results from an online experiment show that the introduction of PLS accounts increase total savings and reduce lottery expenditures significantly, especially among individuals with the lowest levels of savings and income. The results imply that PLS accounts offer a plausible market-based solution to nudge individuals to increase savings.
Keywords: E21; D14; C91; L83; D12; 330; savings; individual decision making; personal finance; lotteries; experimental economics; Sparen; Entscheidung; Private Finanzplanung; Glücksspiel; Test